Evolução do uso e valorização das espécies madeiráveis da Floresta Estacional Decidual do Alto-Uruguai, SC - Ademir Roberto Ruschel; Eunice Nodari Sueli; Miguel Pedro Guerra; Rubens Onofre Nodari (Ciência Florestal, 2003)
Species identification and their market value and price evolution since the colonization time of the remnants of the Brazilian Semi-Evergreen Forest (Floresta Estacional Decidual do Rio Uruguai) for potential timber production was assessed through 41 questionnaires, applied to timbermen and settlers from the surrounding region. The diversity of species for timber production commonly known by the people reached 63. From the 15 predominant species is relevant to mention Apuleia leiocarpa, Parapiptadenia rigida, Balfourodendron riedelianum, Nectandra megapotamica, Patagonula americana, Luehea divaricata, Cedrela fissilis, Ocotea diospyrifolia, Holocalyx balansae, Myrocarpus frondosus, Cabralea canjerana and Peltophorum dubium. The species with the highest commercial value were: Cordia trichotoma, Cedrela fissilis, Myrocarpus frondosus and Balfourodendron riedelianum. Data from the interviews suggest that several species from the Lauraceae family and Schefflera morototoni, Aralia warmingiana, Machaerium stipitatum, Chrysophyllum marginatum had an increment in use and commercial value during the last 15 years. Changing in the commercial value of a species was pointed out as due not only to the timber quality but also to the amount of the timber availability. Overall, it was detected that the species values changed across time and that the timber industry found several ways to adapt to the demands of forest products.